2005
DOI: 10.1518/001872005775570952
|View full text |Cite
|
Sign up to set email alerts
|

Usability of Touch-Panel Interfaces for Older Adults

Abstract: The usability of a touch-panel interface was compared among young, middle-aged, and older adults. In addition, a performance model of a touch panel was developed so that pointing time could be predicted with higher accuracy. Moreover, the target location to which a participant could point most quickly was determined. The pointing time with a PC mouse was longer for the older adults than for the other age groups, whereas there were no significant differences in pointing time among the three age groups when a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 19 publications
3
48
1
2
Order By: Relevance
“…Phillips (2003) found that older adults not only performed better on a pointing task with the mouse, but preferred it as well. Murata and Iwase (2006), however, found that for older adults, pointing on a touch screen was faster than mousing.…”
Section: Direct and Indirect Interactionmentioning
confidence: 91%
“…Phillips (2003) found that older adults not only performed better on a pointing task with the mouse, but preferred it as well. Murata and Iwase (2006), however, found that for older adults, pointing on a touch screen was faster than mousing.…”
Section: Direct and Indirect Interactionmentioning
confidence: 91%
“…Research with older adults has also extended to pointing devices other than the computer mouse, for instance, pen-based input on tablets and handheld computers [Hourcade and Berkel 2008;McGrenere 2007, 2009], touchscreens on touch-panel interfaces, mobile phones, and surfaces [Murata and Iwase 2005;Nicolau and Jorge 2012;Piper et al 2010], and other input devices (e.g., large rollerballs and touchpads) [Taveira and Choi 2009;Wood et al 2005]. These studies aim to better understand and to characterize the nature of older adults' interactions with pointing devices as a basis for informing the design of novel input devices, software interfaces, and assistive techniques.…”
Section: Older Adults and Computer Pointing Devicesmentioning
confidence: 99%
“…First, the ability to physically touch an object on the screen eliminates the need for intermediate interaction devices that must be learned, such as the mouse or joystick. Eliminating this barrier to interaction makes the process simpler, as demonstrated by Murata and Iwase in a study comparing pointing speed for the mouse and a finger [18]. Second, by mimicking the behavior of real-world interactions, direct manipulation makes use of knowledge so fundamental that it seems instinctual.…”
Section: Direct Manipulationmentioning
confidence: 99%